Alteraciones del Sueño y Rendimiento Académico en Adolescentes. - Guano Guisha, Mishel Estefania (2024)
The main objective of this research study was to focus on the literature review that aims to characterize sleep disturbances and academic performance in adolescents, the research design is cross-sectional and descriptive level, had a population of 213 scientific publications belonging to the years 2014-2024 in Spanish and English, the sample was non-probabilistic, made up of 40 scientific articles that allowed to respond to the objectives set out in the research, published in databases such as Pubmed, Scielo, Redalyc, Elvieser, Dialnet, Scopus, ResearchGate and Google Scholar. The methodological quality matrix (CRF-QS) was used to select the articles. Among the most relevant results, it is highlighted that the majority of both male and female adolescents present sleep problems, nocturnal awakenings, excessive daytime sleepiness and insomnia. In addition, these sleep disturbances are related to academic performance, since lack of sleep can negatively disrupt academic performance. In conclusion, lack of sleep can affect concentration, information retention and problem solving, accompanied by emotional consequences such as stress, anxiety and depression. Therefore, these results will help to propose intervention strategies for adolescents to reduce these problems.